Separation properties and n-point topological extensions (1990)
A topological extension of a topological space (X, j) is a topological space (X*,j*) containing (X,j) as a dense subspace. Two topological extensions (X*,j*), and (X*1,j*1) of (X,j) are said to be equivalent if there is a homeomorphism h:(X*,j*) +(X*1,j*1) such that hlX = idx.